2018
DOI: 10.3892/ijo.2018.4492
|View full text |Cite
|
Sign up to set email alerts
|

A miR-26a/E2F7 feedback loop contributes to tamoxifen resistance in ER-positive breast cancer

Abstract: Tamoxifen (TAM) resistance is a substantial challenge in the treatment of estrogen receptor (ER)-positive breast cancer. Previous studies have revealed an important role of microRNA (miRNA/miR)-26a in TAM resistance in breast cancer. However, the mechanism underlying the regulatory effects of miR-26a on TAM resistance remains to be elucidated. The expression levels of miR-26a in ER-positive breast cancer were detected by reverse transcription-quantitative polymerase chain reaction. E2F transcription factor 7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
(52 reference statements)
1
30
0
Order By: Relevance
“…OncoTargets and Therapy 2020:13 11910 cells. 33 Wang et al demonstrated that E2F7 abundance was enhanced in NSCLC tissues, and miR-935 restrained NSCLC progression through targeting and reducing E2F7 expression. 21 E2F7 was confirmed as a target of miR-33a-5p in NSCLC cells, and E2F7 silencing overturned circ_SATB2-mediated effects in Cela-treated NSCLC cells, suggested that circ_SATB2 functioned in Celastimulated NSCLC cells through enhancing E2F7 expression.…”
Section: Dovepressmentioning
confidence: 99%
“…OncoTargets and Therapy 2020:13 11910 cells. 33 Wang et al demonstrated that E2F7 abundance was enhanced in NSCLC tissues, and miR-935 restrained NSCLC progression through targeting and reducing E2F7 expression. 21 E2F7 was confirmed as a target of miR-33a-5p in NSCLC cells, and E2F7 silencing overturned circ_SATB2-mediated effects in Cela-treated NSCLC cells, suggested that circ_SATB2 functioned in Celastimulated NSCLC cells through enhancing E2F7 expression.…”
Section: Dovepressmentioning
confidence: 99%
“…An MTT assay was used to measure the cell viability of MCF-7 and MDA-MB-231 lines. At 24 h post-transfection, cells were seeded in 96-well plates at a density of 4x10 3 cells/well and cultured for 24, 48 and 72 h. Then, the MTT assay was conducted as previously described (26).…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…E2F7 has been found to be overexpressed in primary blasts isolated from patients with acute myeloid leukemia (AML), where it promoted cell cycle progression and inhibited the monocytic differentiation of AML cells ( 10 ). A previous study suggested that miR-26a and E2F7 may form a double-negative feedback loop, resulting in the downregulation of miR-26a and upregulation of E2F7 in estrogen receptor-positive breast cancer, where Both miR-26a knockdown and E2F7 overexpression conferred resistance to tamoxifen in MCF-7 cells ( 11 ). In addition, E2F7 has also been demonstrated to be overexpressed in cutaneous squamous cell carcinoma compared with that in normal epidermis, where suppression of E2F7 expression in a squamous cell carcinoma cell line resulted in increased UV-induced and doxorubicin-induced apoptosis ( 12 ).…”
Section: Introductionmentioning
confidence: 99%